2007
DOI: 10.1007/s11373-007-9192-0
|View full text |Cite
|
Sign up to set email alerts
|

siRNA targeting midkine inhibits gastric cancer cells growth and induces apoptosis involved caspase-3,8,9 activation and mitochondrial depolarization

Abstract: Midkine (MK), a heparin-binding growth factor, is expressed highly in various malignant tumors, so it acts as attractive therapeutic target. In the present study, we used siRNA targeting MK to downregulate human MK expression in human gastric cancer cell line BGC823 and SGC7901 so as to determine the advantages of this anticancer therapeutic. The cell proliferation was evaluated by a WST-8 (4-[3-(2-methoxy-4-nitrophenyl)-2-(4-nitrophenyl)-2H-5-tetrazolio]-1, 3-benzene disulfonate sodium salt) assay and colony … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…This protein is overexpressed in various human malignancies, including bladder, prostate, breast, lung, liver, and colon tumors, although its expression is typically low or undetectable in normal adult tissues (8 -10). In tumors, MDK exhibits angiogenic (11), mitogenic (12), and antiapoptotic activities (13). Its expression in tumors (8,14) and its concentration in plasma (15) are associated with a poor disease outcome.…”
Section: Midkine (Mdk)mentioning
confidence: 99%
“…This protein is overexpressed in various human malignancies, including bladder, prostate, breast, lung, liver, and colon tumors, although its expression is typically low or undetectable in normal adult tissues (8 -10). In tumors, MDK exhibits angiogenic (11), mitogenic (12), and antiapoptotic activities (13). Its expression in tumors (8,14) and its concentration in plasma (15) are associated with a poor disease outcome.…”
Section: Midkine (Mdk)mentioning
confidence: 99%
“…We previously also found that MK was highly expressed in the gastric tumor tissues of Chinese patients and patients with malignant effusions [25, 26]. Both siRNA targeting MK gene and the conjugate (a single-chain variable fragment against human MK-Doxorubicin) inhibited gastric cancer cell growth and induced apoptosis [27, 28]. MK is therefore an attractive molecular target for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the fact that in normal developing mouse embryos MK gene and protein play a role in cell differentiation and organogenesis [25] , these results suggested that MK mRNA and protein along with ER-β mRNA and protein may have some relationship to the lung cancer cell differentiation in NSCLC. Another earlier study [28] in our lab indicated that small interfering RNA (siRNA) targeting MK gene can inhibit gastric cancer cell growth and induce apoptosis via mitochondrial depolarization and caspase-3 activation, which suggested that MK siRNA may be a promising novel and potential therapeutic strategy for the treatment of gastric cancers. Therefore, MK siRNA should also be a good candidate for treating NSCLC.…”
Section: Discussionmentioning
confidence: 95%